C-glycosylflavones from the leaves of Iris tectorum Maxim. - Yuhan Ma; Huan Li; Binbin Lin; Guokai Wang; Minjian Qin (Elsevier, 2012)
A new C-glycosylflavone, 5-hydroxyl-4',7-dimethoxyflavone-6-C-[O-(α-l-3'''-acetylrhamnopyranosyl)-1→2-β-d-glucopyranoside] (1), along with five known C-glycosylflavones, 5-hydroxy-4',7-dimethoxyflavone-6-C-[O-(α-l-2'''-acetylrhamnopyranosyl)-1→2-β-d-glucopyranoside] (2), embinin (3), embigenin (4), swertisin (5) and swertiajaponin (6) were isolated from the leaves of Iris tectorum Maxim. Their structures were elucidated on the basis of extensive NMR experiments and spectral methods and their cytotoxic activities against A549 (lung cancer) human cell lines were determined.